From Sand Hill to Pine - Harte, Bret, 1836-1902 (Salt Lake City, UT : Project Gutenberg, 2006)
"From Sand Hill to Pine" by Bret Harte is a piece of fiction written in the late 19th century. The book begins with a group of passengers aboard a stagecoach led by a driver named Yuba Bill, who faces an unexpected obstacle on their journey a fallen tree across the road. The story hints at underlying tensions and mystery, particularly surrounding a previous robbery of a stagecoach just six months prior, which adds to the atmosphere of suspense and intrigue as the passengers navigate this precarious situation. The opening portion introduces several key characters, including the cautious expressman Ned Brice and a group of miners and workingmen as they deal with the unexpected halt. The scene escalates as they encounter a mysterious stranger who is seemingly helpful but raises questions about their safety. An air of suspicion looms over the passengers, accentuated by references to the past robbery. As the narrative unfolds, more characters are introduced in a settler's cabin, where humor and tension blend as they interact with a young girl connected to the infamous outlaw Snapshot Harry. This dynamic sets the stage for further adventures and conflicts, making readers curious about how these intertwining stories will evolve. (This is an automatically generated summary.)
A niece of Snapshot Harry's -- A treasure of the redwoods -- A belle of Cañada City -- What happened at the fonda -- A Jack and Jill of the Sierra -- Mr. Bilson's housekeeper
Release date is 2006-05-18
Produced by Donald Lainson; David Widger
Keywords: Short stories; American fiction -- 19th century